Proteomics and weighted gene correlated network analysis reveal glutamatergic synapse signaling in diazepam treatment of alcohol withdrawal - Kong, Wan; Huang, Shanqing; Chen, Zikai; Li, Xiaolin; Liu, Shujing; Zhang, Zi; Yang, Ye; Wang, Zhanzhang; Zhu, Xiuqing; Ni, Xiaojia; Lu, Haoyang; Zhang, Ming; et al. (Frontiers in Pharmacology, 2023)
Alcohol use disorder (AUD) is characterized by chronic excessive alcohol consumption, often alternating with periods of abstinence known as alcohol withdrawal syndrome (AWS). Diazepam is the preferred benzodiazepine for treatment of AWS under most circumstances, but the specific mechanism underlying the treatment needs further research. We constructed an animal model of two-bottle choices and chronic intermittent ethanol exposure. LC-MS/MS proteomic analysis based on the label-free and intensity-based quantification approach was used to detect the protein profile of the whole brain. Weighted gene correlated network analysis was applied for scale-free network topology analysis. We established a protein–protein interaction network based on the Search Tool for the Retrieval of Interacting Genes (STRING) database and Cytoscape software, and identified hub proteins by CytoHubba and MCODE plugins of Cytoscape. The online tool Targetscan identified miRNA–mRNA pair interactions. Seven hub proteins (Dlg3, Dlg4, Shank3, Grin2b, Camk2b, Camk2a and Syngap1) were implicated in AWS or diazepam treatment. In enrichment analysis, glutamatergic synapses were considered the most important pathway related to AUD. Decreased glutamatergic synapses were observed in the late stage of withdrawal, as a protective mechanism that attenuated withdrawal-induced excitotoxicity. Diazepam treatment during withdrawal increased glutamatergic synapses, alleviating withdrawal-induced synapse inhibition. Glutamatergic synapses are considered the most important pathway related to AUD that may be a potential molecular target for new interventional strategies.